Non-Conventional Monetary Policy: The Case of Bolivia - Rivero, Roger Alejandro Banegas; RamÃrez, Marco Alberto NÃºÃ±ez; RÃo, SacnictÃ© Valdez del (International Journal of Economics and Financial Issues, 2018)
In this paper, we quantify the role of non-conventional monetary policy for Bolivia. The results suggest that changes in the real assets of the central bank show differentiated effects: contractive policy has more negative and significant effects on the real business cycle, in contrast to its expansive orientation. These results are robust to an econometric battery by alternative models (VAR, SVAR Short-Run, SVAR Long-Run, BVAR), for the quarterly period from 2000 (Q1) to 2015 (Q4). The excess growth of the M2 aggregate in relation to M1 exerts greater variability in the short-term fluctuations of output gap, in comparison with the real assets of central bank. Keywords: Non-Conventional Monetary Policy, Output Gap, Asset of Central Bank Inflation, Interest Rate, SVAR. JEL Classifications: C36, E31, E32, E43, E52, E58